2018
DOI: 10.1016/bs.ctdb.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Physical and Biochemical Properties of the Extracellular Matrix Regulate Cell Fate

Abstract: The extracellular matrix is a complex network of hydrated macromolecular proteins and sugars that, in concert with bound soluble factors, comprise the acellular stromal microenvironment of tissues. Rather than merely providing structural information to cells, the extracellular matrix plays an instructive role in development and is critical for the maintenance of tissue homeostasis. In this chapter, we review the composition of the extracellular matrix and summarize data illustrating its importance in embryogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
163
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(165 citation statements)
references
References 209 publications
1
163
0
1
Order By: Relevance
“…For example, the positive impact of bioreactors in musculoskeletal tissue engineering has been well-established (Peroglio et al, 2018) and electrospun scaffolds coupled with bioreactors have shown promise todate, even for complex structures, such as the cartilage-bone interface (Baumgartner et al, 2019). Further, considering that extracellular matrix is key modulator of cell fate through provision of biophysical, biochemical, and biological signals Watt and Huck, 2013;Kumar et al, 2017;Muncie and Weaver, 2018;Smith et al, 2018;Novoseletskaya et al, 2019), strategies that enhance and accelerate native extracellular matrix synthesis [e.g., hypoxia (Taheem et al, 2019)] and deposition [e.g., macromolecular crowding ] coupled with electrospinning are likely to lead to more biomimetic three-dimensional cartilage equivalents. It is also worth noting, that although the cell-sheet/scaffold-free technology has shown promise in human cartilage engineering (Sato et al, 2019), only thin layers of tissue can be developed, which imposes the need of either multi-layered approaches that are often associated with delamination and cell death in the middle layers due to poor nutrient/waste transport (Sekine et al, 2011) or multiple surgeries (Shimizu et al, 2006;Komae et al, 2017).…”
Section: Critical Analysis and Outlookmentioning
confidence: 99%
“…For example, the positive impact of bioreactors in musculoskeletal tissue engineering has been well-established (Peroglio et al, 2018) and electrospun scaffolds coupled with bioreactors have shown promise todate, even for complex structures, such as the cartilage-bone interface (Baumgartner et al, 2019). Further, considering that extracellular matrix is key modulator of cell fate through provision of biophysical, biochemical, and biological signals Watt and Huck, 2013;Kumar et al, 2017;Muncie and Weaver, 2018;Smith et al, 2018;Novoseletskaya et al, 2019), strategies that enhance and accelerate native extracellular matrix synthesis [e.g., hypoxia (Taheem et al, 2019)] and deposition [e.g., macromolecular crowding ] coupled with electrospinning are likely to lead to more biomimetic three-dimensional cartilage equivalents. It is also worth noting, that although the cell-sheet/scaffold-free technology has shown promise in human cartilage engineering (Sato et al, 2019), only thin layers of tissue can be developed, which imposes the need of either multi-layered approaches that are often associated with delamination and cell death in the middle layers due to poor nutrient/waste transport (Sekine et al, 2011) or multiple surgeries (Shimizu et al, 2006;Komae et al, 2017).…”
Section: Critical Analysis and Outlookmentioning
confidence: 99%
“…Beyond the cellular component, TME shows a noncellular component, defined as an extracellular matrix (ECM), which is composed of macromolecules such as collagens, glycoproteins, and proteoglycans as well as integrins [ 19 , 20 ]. ECM, by both structure remodeling and a continuous crosstalk between tumor cells and the TME, regulates extracellular cues from the microenvironment in order to maintain CSC stemness or to promote differentiation into heterogeneous tumor phenotypes.…”
Section: Stemness: An Overview On Its Relevance In Cancer Developmmentioning
confidence: 99%
“…While the first issue is lessened with the use of a simple, portable electrospinning device, biomimicry can be increased with fibre modifications. Relevantly, a highly specialised ECM plays an instructive role in modulating cell behaviour, including the regulation of development, migration, function, and tissue repair [ 16 ]. By providing mechanical support and preferential attachment sites, an electrospun scaffold can guide cell proliferation (i.e., achieving directional growth) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, as a highly hydrophobic material, it is associated with decreased adhesion and reduced cell growth on its surface [ 3 ]. As such, it is necessary to combine it with another material in order to improve its surface chemistry and, especially, mimic certain topographic features of the ECM [ 16 ]. Gelatine, on the other hand, has excellent biocompatibility, is biodegradable, non-immunogenic and is an inexpensive material that may provide an additional 3D architecture for tissue engineering scaffolds [ 3 ].…”
Section: Introductionmentioning
confidence: 99%